Efektivitas dan Pengaruh Kombinasi Anestesi Ketamine-Xylazine pada Tikus (Rattus norvegicus) - Ita Krissanti; Rifaati Hanifa; Resti Gradia Dwiwina (Gunung Djati Conference Series, 2023)
Anesthesia is used in several studies to reduce or eliminate pain and suffering in experimental animals. One of the most widely used experimental animal species in research is rat (Rattus norvegicus). Ketamine-xylazine (KX) is a combination that is often used for injection anesthesia in rats. The properties of the KX combination ideally can induce the desired effect, such as analgesics, muscle relaxation, and sedation. However, the KX combination can cause side effects that affects the physiological function in rat’s body. This literature study discusses the variety of ketamine-xylazine combination doses that can be used as anesthesia in rats, their effect on cardiorespiratory parameters and body temperature in rats. It can be concluded that the combination of ketamine-xylazine provides a variety of doses that produce a fast onset of action and a duration of action that can be adjusted according to needs.